Badania nad świadomością projakościową studentów wrocławskich uczelni wyższych - Zymonik, Janusz (Research on Promoting Quality Awareness among Students of Selected Wrocław Higher Education Institutions, 2008)
The paper discusses the issues of influencing quality awareness among employees and managerial staff in enterprises. The results of poll research on quality awareness among students starting the "Quality Management" course at three higher education institutions in Wrocław have been presented. The research was carried out in accordance with the established criteria. The results of the research were interpreted, and on this basis conclusions and suggestions for lecturers conducting the "Quality Management" course have been formulated. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 31, s. 202-211